Effect of processing parameters on friction and damage of carbon yarn during three-dimensional weaving. Issue 6 (3rd June 2022) - Li, Siyuan; Shan, Zhongde; Du, Dong; Zhan, Li; Guo, Zitong; Du, Wudi; Wu, Xiaochuan
Abstract: The main structure of a fiber-reinforced composite is determined by a preform. The manufacturing of preforms is associated with the generation of fiber hairiness or even breakage due to friction, which can compromise the properties of the final composite component. This study simulated the frictional behavior of carbon fibers during flexible oriented three-dimensional weaving to determine the processing parameters that affect yarn damage. The normal load and rubbing angle affected the generation of hairiness, while tension was the main factor for yarn damage. However, sliding frequency had a minimal effect. Therefore, the normal load and tension must be controlled during weaving, while weaving speed can be increased while ensuring the stability of the weaving process. These findings provide an experimental and theoretical basis for reducing damage during preform weaving.